أثر تقنيات عرض المنتجات على السلوك الشرائي للمستهلك - متجر فاميلي شوب تيسمسيلت نموذجا - بلال, فاطمة الزهراء; لجلط, إبراهيم (جامعة الوادي - University of Eloued, 2022)
هدفت الدراسة إلى التعرف على أثر تقنيات العرض للمنتجات على السلوك الشرائي للمستهلك في متجر Family shop بتيسمسيلت، حيث أن تقنيات العرض المنتجات تتم وفقا للبعدين )الجو العام المهيأ لعرض المنتجات، السياسات التسويقية المطبقة لعرض المنتجات ) حيث أجريت الدراسة على عينة عشوائية من المستهلكين بمتجر Family shop بتيسمسيلت تتكون من 60 مستهلك . توصلت الدراسة إلى وجود أثر ذو دلالة إحصائية بين تقنيات العرض للمنتجات و السلوك الشرائي للمستهلك ، حيث بلغ معامل الارتباط 0,04 عند مستوى معنوية ( α≤ 0.05) ، بين المتغيرين وجاء بعد الجو العام المهيأ لعرض المنتجات في المرتبة الأولى. The study aimed to identify the impact of display techniques for products on the consumer buying behavior of the Family Shop in Tissemsilt, and the techniques for displaying products are carried out according to the two dimensions (the general atmosphere of the display of products, the shopping policies applied to display the products) - the study was conducted on a random sample of consumers of the family shop in Tissemsilt Consists of 60 consumers. The study concluded that there is a statistically significant effect between the display techniques of products and the purchasing behavior of the consumer, where the rank coefficient reached 0.04 at the level of significance (<0.05), (between the two variables, and this general atmosphere prepared for displaying products ranked first. Keywords: displaying products, display techniques, products, general atmosphere, longing policies, consumer purchasing behavior
The impact of product display techniques on consumer purchasing behavior, a family tissmsilt shop mode
مقال
Keywords: عرض المنتجات ; تقنيات عرض المنتجات ; الج ; العام ; السياسات التس ; يقية السل ; ك الشرائي للمستهلك